Avaliação do comportamento biomecânico e sobrevivência de coroas unitárias em zircônia sobre pilares cad/cam e implantes confeccionados por impressões 3d - Lopes, Guilherme da Rocha Scalzer (Universidade Estadual Paulista (UNESP), 2026)
This study aimed to evaluate the fatigue behavior and reliability of two types of CAD/CAM abutments used for single implant-supported reconstructions. Additively manufactured implants with an internal conical connection (4 x 10 mm; Plenum, Jundiaí, SP, Brazil) were used. Half of the implants received Ti-base abutments while the other half received proprietary Plenum abutments (both Ø 4.5 x 1 mm). Zirconia crowns were milled and cemented onto the abutments. Representative specimens were characterized using EDX, XRD, and SEM. Eighteen specimens per group were subjected to step-stress accelerated life testing (15 Hz) through 30 degrees off-axis load application using three loading profiles: mild, moderate, and aggressive until failure or suspension. Failure load and number of cycles were used to calculate use- level probability curves, fatigue beta values, and reliability for 100,000- cycle missions at 50 and 100 N followed by failure-mode analysis. Characterization results confirmed the alloy was composed of titanium, aluminum, vanadium, without β phase. SEM images show a rough but uniform surface. In fatigue testing, β values (>1) suggested failures due to fatigue damage accumulation. Considering the β lower bounds (<1), two- parameter Weibull analysis was conducted (95% CI) revealing no significant differences regarding modulus between groups. However, Ti-base abutments presented higher characteristic strength (140.2 N [134.9-145.7]) compared to Plenum abutments (99.2 N [93.4- 105.2]). For missions at 50 N both groups presented high reliability (≥99%). At 100 N, reliability for Plenum abutments decreased significantly (25%), while the Ti-base group remained above 99%. Failure-mode evaluation revealed that Ti-base specimens failed either at the abutment or abutment-screw, whereas all failures in the Plenum group involved the abutment-screw assembly. Ti- base presented higher characteristic strength and reliability than Plenum abutments. Both abutments on 3D-printed implants presented high reliability for physiologic masticatory forces in the anterior region.
Evaluation of the biomechanical behavior and survival of single zirconia crowns on CAD/CAM abutments and implants manufactured by 3D printing
Keywords: Cerâmica; Implantes dentários; Materiais dentários; Dental Implants; Dental materials; Ceramics